EXPLORING SELF-CONFIDENCE IN SPEAKING ENGLISH: A STUDY OF USERS` EXPERIENCES ON THE EPISODEN PLATFORM - Rina Dewi, Novi; Utami, Sri (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
In the digital era, the use of technology in language learning has created new opportunities for English learners to practice speaking in more flexible and interactive ways. One such innovation is the Episoden platform, which provides real-time, one-on-one speaking sessions with users from different countries. For many learners, especially non-native Speakers, confidence remains a major obstacle in speaking English fluently and spontaneously. This study aimed to explore users` self-confidence in speaking English through their personal experiences on the Episoden platform. Specifically, the research focused on Identifying how users describe their confidence-building process and what factors influence their confidence, A qualitative descriptive approach was chosen to gain deeper insight into users`Experiences. Using an open-ended questionnaire, semi-structured interviews, observation, and documentation. The data were analyzed through the flow model by Miles and Huberman, consisting of data reduction, display, and conclusion drawing.The results indicated that users became more confident over time through regular use of Episoden. Supportive conversations, clear topics, and a non-judgmental atmosphere were key factors, while common challenges like accents and technical issues helped build speaking routines. In conclusion, Episoden supports users in building self-confidence by providing real practice and a safe space to communicate and take risks.